Catalytic asymmetric desymmetrization of diesters: advances and perspectives - Yu Huang; Jia-Yu Liao (Tetrahedron Chem)
Catalytic asymmetric desymmetrization of prochiral and meso-diesters has emerged as a powerful strategy for the synthesis of chiral compounds featuring tertiary or quaternary stereogenic carbon centers. This mini-review summarizes the recent progress in this rapidly growing field. The reported fruitful examples have been organized and presented according to their reaction types. In the end, a perspective on the current limitations and future opportunities is provided to inspire further developments in this area.